Review of the ADB energy program. ([Manila] Asian Development Bank, 2020)
A decade after the Clean Energy Program took form, the review determines how far the bank has gone toward achieving its targets vis-a-vis baseline data from 2005 to 2007. It also explores what must to be done further in light of the new approach under ADB Strategy 2030 and the global goals in mitigating climate change and promoting sustainable development.
Keywords: Climate change; Electronic books